Organocatalytic Enantioselective Friedel–Crafts Reaction of Phenanthrenequinones and Indoles - Yan Jin; Yuhong Sun; Yue Yu; Jiao Zhao; Mingshan Zheng; Liming Wang; Ying Jin (Molecules)
An efficient stereoselective synthesis of 10-hydroxy-10-(1H-indol-3-yl)-9-(10H)-phenanthrene derivatives was realized through an organocatalyzed Friedel–Crafts reaction of phenanthrenequinones and indoles using a (S,S)-dimethylaminocyclohexyl-squaramide as the catalyst. Under the optimized conditions, the desired chiral products were obtained in good yields (73–90%) with moderate to high ee values (up to 97% ee). Two pairs of synthesized enantiomers were subjected to evaluation of their antiproliferative activities on four types of human cancer cell lines and one human umbilical vein endothelial cell line using the CCK-8 assay. The results indicated that stereoselectivity had obvious impacts on biological activity. (S)-4g was found to have optimal cytotoxicity against the A549 cell line and a good safety profile for human normal cells, which was better than the inhibitory activity of the positive control drug (doxorubicin).